2006
DOI: 10.1590/s1415-47572006000100010
|View full text |Cite
|
Sign up to set email alerts
|

X monosomy and balanced Robertsonian translocation in a girl with Turner Syndrome

Abstract: We describe a case of X monosomy associated with a maternally inherited t(13;14) Robertsonian translocation in a girl with Turner syndrome. The girl's X chromosome was demonstrated to be maternally inherited, ruling out the hypothesis that the translocation exerted an interchromosomal effect on the origin of the monosomy. Chromosomes 13 and 14 showed biparental inheritance. Key words: Robertsonian translocation, X monosomy, interchromosomal effect. It has been suggested that chromosomal rearrangements may dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 6 publications
(5 reference statements)
0
12
0
Order By: Relevance
“…Krajinovic et al (1994) found that both X-chromosomes and the t(13;14) were paternally inherited in one of their patients. Silva et al (2006) reported a patient who had both translocation and X-chromosome that were demonstrated to be maternally inherited. All of these studies reported the association between balanced Robertsonian translocations and Turner's syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Krajinovic et al (1994) found that both X-chromosomes and the t(13;14) were paternally inherited in one of their patients. Silva et al (2006) reported a patient who had both translocation and X-chromosome that were demonstrated to be maternally inherited. All of these studies reported the association between balanced Robertsonian translocations and Turner's syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, four cases of monosomy X associated with balanced Robertsonian translocation t(13;14) (Laszlo et al, 1984;Salamanca et al, 1985;Krajinovic et al, 1994;Silva et al, 2006) and one previous case of Turner's syndrome with familial balanced translocation t(1;2) (q32;q21)mat (Kondo et al, 1979) have been reported until now.…”
Section: Introductionmentioning
confidence: 99%
“…Using high resolution banding, Ozkul et al (2002) found a TS infant with the karyotype 45X,t(1;2)(q41;p16), and one case of TS with familial balanced translocation t(1;2)(q32;q21)mat was described by Kondo et al (1979). Four other studies reported an association of X-monosomy with balanced Robertsonian translocation t(13;14) (Laszlo et al, 1984;Salamanca et al, 1985;Krajinovic et al, 1994;Silva et al, 2006). Recently, Djordjević et al (2010) showed a case of 45,X,t(1;9) (cen;cen) in combination with a r(X) mosaic karyotype.…”
Section: Discussionmentioning
confidence: 98%
“…The coexistence of a balanced translocation and a chromosome X abnormality in Turner syndrome patients is rarely reported in the literature [4–10]. Four cases were carriers of a parentally transmitted Robertsonian translocation and had the non mosaic 44,X,t(13;14)(q10;q10) karyotype [4–7].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Xp or Xq deletions and ring (X) chromosomes may also be observed during cytogenetic analyses [3]. Coexistance of an familially transmitted autosomal translocation and Turner syndrome karyotype is a rare phenomenon and only a few cases were reported in the literature [4–10]. We here present a 16-year-old Turner syndrome patient who had an isochromosome of the long arm of chromosome X in a mosaic form and, like her mother, familial reciprocal translocation between chromosomes 4 and 16.…”
Section: Introductionmentioning
confidence: 99%